2021
DOI: 10.21037/atm-21-1078
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap formation index predicts occurrences of deep surgical site infection after laparotomy

Abstract: Background: Deep surgical site infections (DSSIs) are serious complications after laparotomy. Neutrophil extracellular traps (NETs) play a vital role in the development of DSSI. Here, we focused on a new approach to predicting the occurrence of DSSI through the detection of the NET formation index (NFI), and compared its prediction ability with other clinical infection indicators. Methods: Patients who received laparotomy were prospectively enrolled in this study. General information, APACHE II score, SOFA sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, overproduction of NETs may lead to local tissue damage, and NETs may act as a proinflammatory agent [ 8 ]. Our previous research has demonstrated that circulating NET biomarkers are linked to disease severity and clinical prognosis [ 15 , 53 ]. In the current study, we observed similar findings, as both MPO-DNA and CitH3-DNA complexes, which serve as intestinal NET biomarkers, were found to be elevated in serum and intestinal samples obtained from patients experiencing II/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, overproduction of NETs may lead to local tissue damage, and NETs may act as a proinflammatory agent [ 8 ]. Our previous research has demonstrated that circulating NET biomarkers are linked to disease severity and clinical prognosis [ 15 , 53 ]. In the current study, we observed similar findings, as both MPO-DNA and CitH3-DNA complexes, which serve as intestinal NET biomarkers, were found to be elevated in serum and intestinal samples obtained from patients experiencing II/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that the recruitment and activation of neutrophils at the site of injury may contribute to adhesion formation through the release of pro-inflammatory mediators and the promotion of fibroblast activation [ 12 , 13 , 14 ], raising further questions on their particular significance. Duan Z et al’s work revealed that measuring the neutrophil extracellular trap formation index (NFI) in postoperative drainage fluid offers a more sensitive and specific method for early prediction of deep surgical site infections compared to traditional serum infection indicators like CRP and PCT [ 15 ]. Consequently, the objective of this review was to examine research focusing on the role that neutrophils play in abdominal adhesions.…”
Section: Introductionmentioning
confidence: 99%